Platelet Associated Fibrinogen and ICAM-2 Induce Firm Adhesion of Neutrophils under Flow Conditions - Kuijper, P. H. M.; Torres, H. I. Gallardo; Lammers, J.-W. J.; Sixma, J. J.; Koenderman, L.; Zwaginga, J. J. (Thrombosis and Haemostasis, 1998)
Surface-bound platelets support selectin-mediated rolling and β2-integrin-mediated firm adhesion of neutrophils (PMN) under flow conditions. We examined which ligands on platelets mediate this firm adhesion. Surface-bound platelets express ICAM-2 and GPIIbIIIa-bound fibrinogen, which are ligands for LFA-1 and MAC-1. In a well defined model for vessel wall injury, blood from an afibrinogenemic patient was perfused over ECM-coated coverslips to obtain fibrinogen-free platelet surfaces. At high shear rates, PMN-adhesion to fibrinogen-free platelet surfaces decreased compared to fibrinogen-containing controls. Under these conditions, firm adhesion and not rolling was blocked demonstrating the importance of fibrinogen in this process. In addition, MAC-1 and LFA-1 on PMN and ICAM-2 on platelets played a role in firm adhesion; the effect of blocking antibodies was most evident at high shear. The effects of fibrinogen depletion and ICAM-2 blocking were additive. In conclusion, multiple redundant ligands, like ICAM-2 and fibrinogen, induce firm and shear resistant PMN adhesion to platelets under flow conditions. Individually these ligands become critical at higher shear. Blocking of two or more interactions also interferes with low shear adhesion.